2019
DOI: 10.1186/s12891-019-2492-5
|View full text |Cite
|
Sign up to set email alerts
|

Superselective angiography of the wrist in patients with Kienböck’s disease

Abstract: Background Microvascular problems like increased intraosseous pressure or venous congestion may influence the development of Kienböck’s disease. We examined if wrist position modifies the blood flow in the nutrient vessels. Methods Retrospective analysis of 17 patients with Kienböck’s disease who had a superselective microangiography of the radial, ulnar and interosseous artery in different wrist positions under general anaesthesia. We analysed the data with Fisher’s ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Depending on the degree of damage there are several surgical options available: Revascularization, capitates-shortening osteotomy, joint leveling, metaphyseal core decompression, proximal row carpectomy, fusion, and arthroplasty (Frerix et al, 2016;Hong et al, 2019;Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the degree of damage there are several surgical options available: Revascularization, capitates-shortening osteotomy, joint leveling, metaphyseal core decompression, proximal row carpectomy, fusion, and arthroplasty (Frerix et al, 2016;Hong et al, 2019;Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a secondary analysis of the study described in “ Superselective angiography of the wrist in patients with Kienbock’s disease ” [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…During routine clinical practice, wrist surgeons are also recurrently faced with the challenge of evaluating possibilities for vascularized bone grafts in complex cases. Publication of our primary work [ 18 ] triggered the hope for a reproduciable imaging tool to measure the peripheral arteries of the wrist as another application of SCAW.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Recently Kim et al showed the wrist position-dependent perfusion of the lunate using super-selective angiography of the radial, ulnar, and interosseous artery. 31 They found the maximum blood flow during neutral wrist position, which decreased with extension or flexion of the wrist. They concluded that prolonged wrist flexion or extension in pain or splinting, occupation might contribute to the pathogenesis of the disease.…”
Section: Vascular Factorsmentioning
confidence: 96%